Das flussbett making ranking theory useful for the social world (2020)
Epistemology is, at first glance, a specific field on the realm of sciences. Nevertheless, at the same time, epistemology is a general theory of what humans are doing right or wrong in all sciences. Actually, epistemology is about what are we doing right or wrong rationally in all those different fields of science. In this sense, it is a field devoted to achieving knowledge following certain rational justified principles and models. The key question is thus: why ought to follow such principles and models? And, given this, how to establish better, clear, precise and justified models of reasoning to fulfill this normativity task and challenge? The present dissertation is thus devoted to answering such questions in the realm of social sciences. The main goal is to establish an ideal model, a methodological tool-box, for the internal or epistemic normativity of the social sciences thanks to this normative reflection. Following the legacy of Wolfgang Spohn (2011), the dissertation wants to study the epistemic normativity of the social sciences, as a central criterion of its identity and demarcation. The epistemic normativity that subjects follow to the precise understanding of social phenomena, is the core of this specific kind of scientific knowledge, and goes beyond the account of empirical methodologies that appeal to an external normativity that is not exclusive used to the treatment of objects and problems relative to the social sciences.